PSAT : a pairwise test data generation tool based on simulated annealing algorithm - Goh, Ghee Hau (2015)
In this information technology era, there is a huge influence of high technology and artificial intelligence when creating new software products in the whole world. To bring high quality software products to the end user, software testing plays important roles and need to be considered during the development stage. Therefore, there is impossible to cover all the test case of the software products and may lead to exhaustive testing. This research is about the research on developing a Pairwise Test Data Generation Tool based on Simulated Annealing (SA) algorithm which named as PSAT. PSAT is used to generate the sufficient test case to reduce the financial resources and time. In PSAT, we using pairwise testing techniques which each interaction of test case considers of two input parameters. Each parameter will have different parameter values that entering by users. In development of PSAT, a prototype of Graphics User Interface (GUI) will be designed and create for user to enter the number of parameters and number of values for each parameter. In this research, the test case will be generated based on the SA algorithm to show that the test case can be generated with sufficient.